Research On Contemporary Financial Transactions Related To Restaurants Assessed Through Islamic Jurisprudence And Human Health - Salem Farhat, Ali Ahmed; Abdullah Al Mazher, Abdullah Mohammed; Mohammed Al Asmari, Abdullah Ali (Journal of Neonatal Surgery, 2025)
The study aimed to elucidate certain contemporary financial transactions related to restaurants from the perspective of Islamic jurisprudence and human health. It employed a descriptive methodology, supplemented by analytical techniques, yielding several key findings: Financial transactions, as per Islamic rulings, pertain to worldly affairs conducted between two parties involving money circulation through buying, selling, leasing, etc., for profit purposes. There is a consensus among Muslims on the general permissibility of financial transactions, as individuals often require what others possess. Contemporary issues related to restaurants include the ruling on eating to fullness. Some restaurants offer a fixed price for a meal until satiation, which is permissible and considered minor permissible uncertainty that does not affect the sale's validity. Similarly, eating from an open buffet is allowable for the same reasons. The high prices at airport restaurants and cafeterias are due to supply and demand dynamics, fundamental to the pricing of airport restaurant products. It is noted that food and beverages from restaurants must adhere to high-quality standards concerning health requirements. RECOMMENDATIONS Careful investigation of contemporary transactions related to restaurants, explaining them to the public. Linking the legitimacy of certain foods to health stipulations.